2006
DOI: 10.1002/chir.20360
|View full text |Cite
|
Sign up to set email alerts
|

Route‐dependent stereoselective pharmacokinetics of tramadol and its active O‐demethylated metabolite in rats

Abstract: The effects of route of administration on the stereoselective pharmacokinetics of tramadol (T) and its active metabolite (M1) were studied in rats. A single 20 mg/kg dose of racemic T was administered through intravenous, intraperitoneal, or oral route to different groups of rats, and blood and urine samples were collected. Samples were analyzed using chiral chromatography, and pharmacokinetic parameters (mean +/- SD) were estimated by noncompartmental methods. Following intravenous injection, there was no ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 14 publications
2
21
0
4
Order By: Relevance
“…tramadol when used during CO 2 insufflation; this can probably be explained by the fact that tramadol is decomposed in acidic and basic environments [17]. Another explanation has been suggested by Parasprampuria and colleagues [18]. They have shown that in rats the route of administration of tramadol affected the stereoselective pharmacokinetics of this drug; after i.v.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…tramadol when used during CO 2 insufflation; this can probably be explained by the fact that tramadol is decomposed in acidic and basic environments [17]. Another explanation has been suggested by Parasprampuria and colleagues [18]. They have shown that in rats the route of administration of tramadol affected the stereoselective pharmacokinetics of this drug; after i.v.…”
Section: Discussionmentioning
confidence: 92%
“…administration of tramadol, the blood concentration of the enantiomers, although lower than that after the i.v. injection, was substantial and stereoselective in favour of the (1)-enantiomer [18]. The manufactured tramadol is a racemic mixture of two complementary and synergistic enantiomers [15].…”
Section: Discussionmentioning
confidence: 98%
“…The conversion to the M1 metabolite is variable among species, but it is known that it is produced in rats, mice, and rabbits. [78][79][80] In the United States, only the oral formulation is available. In humans, less respiratory depression and constipation are seen with tramadol than with other m-agonist opioids.…”
Section: Meloxicammentioning
confidence: 99%
“…It is active at opiate, alpha-adrenergic, and serotonergic receptors. 90,112,123 In the United States, only the PO formulation is available. The conversion to the M1 metabolite is variable among species, but it is known that it is produced in rats, mice, and rabbits.…”
Section: Tramadol Hydrochloridementioning
confidence: 99%
“…109 Tramadol is a very weak μ agonist, but the O-desmethyl metabolite (M1) is a much more potent agonist. 57 The pharmacokinetics of tramadol have been evaluated in rats 34,90,127 and rabbits, 112 but analgesic plasma concentrations have not yet been established. 90,112,123 In the United States, only the PO formulation is available.…”
Section: Tramadol Hydrochloridementioning
confidence: 99%